JARAK SOSIAL ANTAR MASYARAKAT TRANSMIGRAN DENGAN MASYARAKAT LOKAL DI DUSUN BUKIT INDAH KECAMATAN SUBAH KABUPATEN SAMBAS - Verawati, Tuti; Fatmawati, Fatmawati; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis is "Social Distance Between Transmigrant Communities and Local Communities in Dusun Bukit Indah, Sambas District". This study aimed to determine the social distance between transmigrant communities and local communities in Dusun Bukit Indah, Subah Sub-district, Sambas District. The research method used is qualitative research methods with descriptive research types. The results of the study shows that; social distance between transmigrant communities and local communities in Dusun Bukit Indah, Subah Sub-district, Sambas District occurs due to negative prejudices, stereotypical attitudes, and discriminatory behavior by transmigrant communities towards the local communities; evidenced by the actions of transmigrant communities who do not understand and do not know the culture of the local community, judging the local community is still old-fashioned and selfish, and shifts land ownership that is customarily owned by local communities by planting palm oil independently and making certificates of those lands.Keywords : Social Distance, Prejudice, Stereotype, Discrimination